2005
DOI: 10.1111/j.1440-1797.2005.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular function in children with β‐thalassemia minor

Abstract: On the contrary of children with beta-thalassemia major, renal tubular dysfunction has not been determined in children with beta-thalassemia minor in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…2,3,12 In one study where TPR values were compared between patients with TMin and healthy subjects, no difference was found. 4 However, there have also been studies on the contrary to our results. Aldudak et al 6 and Hamed and Elmelegy 16 reported that TPR levels were significantly lower in patients with TM than in healthy controls.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…2,3,12 In one study where TPR values were compared between patients with TMin and healthy subjects, no difference was found. 4 However, there have also been studies on the contrary to our results. Aldudak et al 6 and Hamed and Elmelegy 16 reported that TPR levels were significantly lower in patients with TM than in healthy controls.…”
Section: Discussioncontrasting
confidence: 96%
“…There have been studies showing FENa levels increased as an indicator of poor renal function in beta thalassemia patients, 5,10-12 whereas there has also been studies suggesting that this parameter showed no difference. 2,4,6,13 Data regarding the significance of alpha-1M excretion in thalassemia are limited. Our study showed that alpha-1M excretion increased in patients with TM and TI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations